Revision of the bathyal fish genus Benthocometes (Teleostei: Ophidiidae) with a new species from off NW Australia - Nielsen, Jørgen G. (Zootaxa, 2010)
The bathyal genus Benthocometes (Teleostei: Ophidiidae) is revised based on 29 specimens from the Atlantic Ocean and the Mediterranean Sea and one from off NW Australia. Examination of the Atlantic and Mediterranean material confirmed the synonomizing of the three Atlantic species, B. robustus, B. armatum and B. muraenolepis. The Australian specimen represents a new species, B. australiensis, differing from B. robustus in e.g. the number of long rakers on the anterior gill arch, the form of the palatine dentition and the predorsal and upper jaw lengths.